EKSPLORASI KEMANDIRIAN BELAJAR MATEMATIKA SISWA SMP DI KOTA MALANG PADA ERA TRANSISI KURIKULUM MERDEKA - Adesintia M.R. Humba; Vinsensius Vinsen; Elita Mega Selvia Wijaya; Rio Febrianto Arifendi (Universitas Tribhuwana Tunggadewi, 2023)
This study aims to explore the profile of mathematics learning independence among junior high school students in Malang City and identify supporting and inhibiting factors during the curriculum transition period. A qualitative approach with a descriptive case study design was employed. Data were collected through observation, in-depth interviews, and documentation across several junior high schools in Malang City, representing diverse school characteristics. Data analysis followed the interactive model by Miles, Huberman, and Saldana. The results indicate that students are in a dynamic adaptation phase but still exhibit high metacognitive dependence on teacher instructions. While differentiated learning provides room for exploration, its success largely depends on the students' mental resilience. These findings emphasize that the teacher's role as a facilitator—integrating cognitive and emotional aspects (Head, Hands, and Heart)—is crucial in reducing math anxiety and fostering learning autonomy. In conclusion, mathematics learning independence in the transition era is not merely a technical skill but a mental attitude requiring an inclusive school ecosystem